(untitled) (PERcursos Linguísticos, 2020)
This article consists of a study of a placard left on the ground of a public square after a rally in defense of sexual and gender freedom. We aims at discussing the meaning construction process, by thinking on the placard wording that manifested support to the fight for sexual and gender freedom, and it did that in the name of Christian love. To achieve our goal, the wording is studied from the so called rebel thought point of view, with emphasis on the Michel Foucault’s thoughts. The study shows that a simple and an apparently innocent placard encompass a complex and dynamic process of meaning construction, what may be of interest not only to discourse analysts and semanticists but also to all those who feel that studies of the meaning construction process can contribute to the social interaction, including those that take place in school spaces.